2015
DOI: 10.1097/meg.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification and detection of new colorectal neoplasms after colorectal cancer screening with faecal occult blood test

Abstract: Risk stratification of adenoma patients, as recommended by the European guidelines, is appropriate for postpolypectomy surveillance after FOBT screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Since the 2012 recommendations, a number of studies have been published that included evaluation of risk among patients with 3-10 adenomas. These studies are consistent in demonstrating that individuals with 3-10 adenomas are at increased risk for advanced neoplasia [25][26][27][28][29][30] and even CRC alone 26,31 on follow-up. However, we were specifically interested in whether there was sufficient evidence to support longer surveillance intervals for patients with 3-4 small (<10 mm) adenomas.…”
Section: Recommended Post-colonoscopy Surveillance Strategies For Reducing Colorectal Cancer Risksupporting
confidence: 67%
See 1 more Smart Citation
“…Since the 2012 recommendations, a number of studies have been published that included evaluation of risk among patients with 3-10 adenomas. These studies are consistent in demonstrating that individuals with 3-10 adenomas are at increased risk for advanced neoplasia [25][26][27][28][29][30] and even CRC alone 26,31 on follow-up. However, we were specifically interested in whether there was sufficient evidence to support longer surveillance intervals for patients with 3-4 small (<10 mm) adenomas.…”
Section: Recommended Post-colonoscopy Surveillance Strategies For Reducing Colorectal Cancer Risksupporting
confidence: 67%
“…Since the 2012 recommendations, additional studies have confirmed and extended the evidence supporting identification of 1 or more adenomas 10 mm size as a high-risk feature. [25][26][27]30,31 A study of 2990 patients from the Netherlands diagnosed with adenoma 1988-2002 and followed through 2008 found size 10 mm was independently associated with 1.7-fold increased risk for metachronous advanced neoplasia (OR, 1.7; 95% CI, 1.2-2.3). 30 A cohort study of 3300 patients diagnosed with adenomas at a large integrated US health care system found that size 10 mm was independently associated with 3.6-fold increased risk for advanced adenoma (OR, 3.6; 95% CI, 2.8-4.5) and 5.2-fold increased risk for CRC on follow-up (OR, 5.2; 95% CI, 1.8-15.1).…”
Section: Recommended Post-colonoscopy Surveillance Strategies For Reducing Colorectal Cancer Riskmentioning
confidence: 99%
“…For identification of interval cancers, detected prior to the next scheduled screening appointment, we developed an evaluation process in which screening registries and cancer registries were linked, including data on causes of death 11 12 13 . Interval post-colonoscopy colorectal cancer was defined as CRC diagnosed after a screening or surveillance exam in which no cancer was detected and before the date of the next recommended exam 11 .…”
Section: Introductionmentioning
confidence: 99%
“…1,42 Colonoscopy screening alone has resulted in a 90% chance of survival and declining CRC incidence rates among adults aged .55 years. 43 However, the survival rate is reduced to ,10% for late diagnosis of metastatic CRC, 1 demonstrating that early detection is key for patient outcomes. The goal is to use defined microbial signatures as a tool to lead to earlier and less invasive methods of CRC diagnosis.…”
Section: Application Of the Microbiome In Crc Prevention And Therapymentioning
confidence: 99%